Anomalous microstructure and tribological evaluation of AlCrFeNiW0.2Ti0.5 high-entropy alloy coating manufactured by laser cladding in seawater. (20th September 2021) - Liang, Hui; Qiao, Dongxu; Miao, Junwei; Cao, Zhiqiang; Jiang, Hui; Wang, Tongmin
Graphical abstract: Highlights: Phases and microstructure of AlCrFeNiW0.2Ti0.5 HEA coating were analyzed by XRD, SEM, EPMA and TEM. HEA coating shows the hardness of 692.5 HV, more than 5 times as substrate. HEA coating exhibits excellent tribological property sliding against YG6 in seawater. Tribo-chemistry reaction products on worn surface reduce the friction and wear. Abstract: To evaluate the potential of high entropy alloys for marine applications, a new high entropy alloy coating of AlCrFeNiW0.2 Ti0.5 was designed and produced on Q235 steel via laser cladding. The microstructure, microhardness and tribological performances sliding against YG6 cemented carbide, GCr15 steel and Si3 N4 ceramic in seawater were studied in detail. The AlCrFeNiW0.2 Ti0.5 coating showed an anomalous 'sunflower-like' morphology and consisted of BCC and ordered B2 phases. The microhardness was approximately 692.5 HV, which was 5 times higher than substrate. The coating showed more excellent tribological performances than Q235 steel and SUS304, a typical material used in seawater environment, sliding against all three coupled balls in seawater. Besides, the wear and friction of AlCrFeNiW0.2 Ti0.5 coating sliding against YG6 in seawater were most mild. The main reason was the generation of Mg(OH)2, CaCO3, metal oxides and hydroxides and the formation of protective tribo-film on the worn surface of AlCrFeNiW0.2 Ti0.5 coating in the process of reciprocated sliding. This would effectively hinder the direct contact between the worn surfaces of AlCrFeNiW0.2 Ti0.5 coating and YG6 ball, resulting in a decrease of friction coefficient and wear rate. Thus the YG6 was an ideal coupled material for AlCrFeNiW0.2 Ti0.5 coating in seawater, and the coating would become a promising wear-resisting material in ocean environment.